STRATEGI KOMUNIKASI DIGITAL DALAM MENJAGA CITRA MEREK BIENTI AGENCY DI MEDIA SOSIAL INSTAGRAM - Rafif Hidayat Inzaghi; Mareta Puri Rahastine (An Nafi': Multidisciplinary Science, 2025)
The rapid development of digital technology has brought major changes in how organizations communicate and interact with their audiences. Social media, especially Instagram, has become a key platform for building brand image, reputation, and long-term relationships with the public. This study was motivated by the growing need for companies and creative agencies to apply effective and sustainable digital communication strategies in maintaining their brand image in an increasingly competitive creative industry. The purpose of this research is to explore how digital communication strategies are applied to maintain brand image through the Integrated Marketing Communication (IMC) approach. This study uses a qualitative descriptive method with data collected through in-depth interviews, observation, and documentation to gain a comprehensive understanding. The findings show that the digital communication strategy focuses on creating organic content that emphasizes educational value, storytelling, and two-way interaction with audiences. Among the seven elements of IMC, the three most dominant are social media marketing, public relations, and interactive marketing. These strategies have proven effective in increasing audience engagement, building public trust, and maintaining a consistent, credible, and positive brand image on social media, particularly on the Instagram platform.